(untitled) (Metallurgy and Foundry Engineering, 2014)
The paper presents the results of studies on reclamation of moulding sand with a new polymeric binder BioCo2. The polymeric binder of new generation – BioCo2 – is an aqueous solution of two-component polymeric composition of poly(acrylic acid) and dextrin. The aim of research was to show whether can recover sand (reclaim) from the used sand. The properties for reuse as a component of moulding sand were discussed. Used sands and reclaim were subjected to analysis designed to show the degree of reclaimability. Assessment of process was based on the following indicators: the amount of dust released during reclamation, loss on ignition, WSR index and the surface morphology of the sand grains.